(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2024)
This article is the result from a project implemented in the province of Sugamuxi, Boyacá on "Organization and Management of rural areas". The province has been characterized by generating economic returns with agricultural production such as potatoes, corn and vegetables, being its primary economic activity. Even so, there is evidence of backwardness due to governmental neglect, since there is no agricultural reform that provides welfare to the peasant population. The purpose is to strengthen knowledge in rural families, allowing them to create solid productive units with greater administrative autonomy based on sustainable objectives, FAO, UNDP, Food Bank oriented to guarantee Food Security as the axis of Local Development. The Participatory Action Research method was applied to get to know and interpret 8 selected municipalities in their diversity. Using the survey and focus group study. Obtaining a real and significant situational diagnosis. We also achieved the empowerment of 80 rural families through administrative training, financial education, community management, business innovation, among others.